Returning Archaeological Objects to Italy. Issue 3 (20th December 2018) - Gill, David W. J.
Abstract: It has been more than 20 years since the raids on the premises at the Geneva Freeport were linked to Giacomo Medici. The seizure of photographic records led to a major investigation of acquisitions by museums and private collectors. This was expanded following the confiscation of archives from Robin Symes and Gianfranco Becchina. Over 350 items have been returned to Italy from North American public and private collections as well as auction houses and galleries. This article reviews the returns and identifies some of the major themes. It also notes some of the unresolved cases both in North America and in Europe and Japan.